Challenges and cross-cultural adaptation of international students at International Islamic University Malaysia (IIUM): A aualitative study - Ramasa Varity (Journal of Education, Social & Communication Studies, 2026)
This study explores the challenges and cross-cultural adaptation experiences of international students at International Islamic University Malaysia. Guided by Cross-Cultural Adaptation Theory, the study examines the challenges encountered by international students, their effects on academic performance, and the coping strategies employed during the adaptation process. A qualitative phenomenological approach was adopted, and data were collected through focus group discussions and semi-structured interviews involving 20 undergraduate international students from diverse cultural backgrounds. The data were analysed thematically to identify recurring patterns and meanings. The findings reveal that international students experience multiple challenges, including language barriers, academic difficulties, discrimination, financial constraints, and cultural differences, which contribute to acculturative stress and negatively influence academic performance, particularly during the initial stage of adaptation. Despite these challenges, students gradually developed adaptive coping mechanisms through self-regulation, social support, and the use of social media platforms. The study concludes that cross-cultural adaptation is a dynamic and continuous process influenced by both individual resilience and contextual support systems. The findings highlight the importance of institutional support in facilitating international students’ adaptation and enhancing their academic success in higher education institutions.